OP0112 Cystic fibrosis related arthritis in adults in south east england. (23rd January 2014) - Jawad, A.; Pákozdi, A.; Watson, D.; Kuitert, L.
Abstract : Background: Although bone and joint manifestations are common in children with cystic fibrosis (CF), they have received little attention in adults. CF-related arthropathy (CFA) is a relatively infrequent complication previously reported to be present in 2-8.5% of the CF population. It usually affects the large joints with recurrent episodes of swelling and stiffness. It may become more persistent with a polyarticular distribution. Less commonly and affecting older patients (2-7%) is hypertrophic osteoarthropathy which is a syndrome characterized by abnormal proliferation of the skin and osseous tissue at the distal parts of the extremities, occurring in association with radiographically confirmed periosteal new bone formation. Objectives: In this study we aimed to assess the frequency and describe the clinical presentation of musculoskeletal complications in adults with CF. Methods: At the time of this study, 143 adult CF patients (range 16-63, 80 males, 63 females, average age 28.5) were under the care of the London Chest Hospital CF Unit. Their medical records, laboratory and radiological results were analysed retrospectively. Results: 19 of 143 CF patients (13.3%) suffered from musculoskeletal problems, of which 10 had CFA (7%). Other diseases included spondyloarthritis, chondromalatia patellae, vitamin D deficiency, back pain and rotator cuff tendinopathy. There were no cases of hypertrophic osteoarthropathy or transient synovitis. Among the CFA patients, 6 were female and 4 were male. The average age at diagnosis was 25 years in the female group (range 23-30) and 38 years in the male group (range 36-43). All patients suffered from polyarthralgia. 5 patients had moderate and 5 had severe underlying CF disease. On screening only one patient tested positive for ANA, all were negative for both RF and anti-CCP antibody. 5 patients had US scan of their affected joints; one had evidence of active synovitis and erosions. There was no radiological evidence of erosive joint disease in any of the patients. All patients received nonsteroidal-antiinflammatory drugs (NSAIDs) as their primary treatment. Due to inadequate clinical response 5 received disease modifying anti-rheumatic drugs (DMARDs) as well (sulphasalazine, hydroxychloroquine or methotrexate). Conclusions: Similar to previous reports, the incidence of CFA in our cohort was 7%. Interestingly, the age of onset was lower for female patients compared to males. Though there was hardly any synovitis clinically, there was evidence of synovial thickening and erosions on US and Doppler. Although NSAIDs usually control symptoms, half of our patients needed DMARDs as well. Early diagnosis and appropriate management is especially important for CF patients, as joint pain, swelling, and limitation of movement may become disabling and interfere with mobility, exercise and chest clearance, all essential components of CF daily treatment schedule. References: [1] Botton E, Saraux A, Laselve H, Jousse S, Le Goff P. Musculoskeletal manifestations in cystic fibrosis. Joint Bone Spine 2003;70(5):327–35. [2] Johnson S, Knox J. Arthropathy in cystic fibrosis. Respiratory Medicine 1994;88(8):567–70. Disclosure of Interest: None Declared